EVALUATION OF THE EFFECTIVENESS OF BASIC TRAINING FOR CIVIL SERVANT CANDIDATES IN IMPROVING PUBLIC SERVICES IN CENTRAL JAVA - Erni Irawati; Endang Larasati; Hardi Warsono; Ida Hayu Dwimawanti (International Journal of Social Science, 2021)
Improving the quality of human resources for the apparatus is carried out through the recruitment of civil servants with more transparency and integrity by screening qualified civil servants, as the main engine for running the government. Furthermore, the development of Human Resources of state civil apparatus becomes the authority of the Region and the assistance task which is assigned to the Region. In this study, four aspects related to the evaluation of the effectiveness of basic training for civil servant candidates were seen; which are as follows, Integrated Competence Development, State Defense Attitudes and Behaviors, Actualization of the Basic Values ​​of Civil Servants, and the Position and Role of Civil Servants in the Unitary State of the Republic of Indonesia. Competence is needed in service functions. Therefore, civil servants need to be equipped with practical education, not just theoretical. Basic Training for the Prospective Civil Servant as the initial provision for Prospective Civil Servants is a strategic training in which there are dominant aspects contained in the learning curriculum to be actualized later in the work and duties of the participants who are functions as civil servants. Curriculum development and learning systems that emphasize the transfer of culture or how those values ​​will be integrated in the attitudes and behavior of the apparatus, become a culture, work ethic that supports the professionalism of their duties and positions. Analysis of the effectiveness of the results of the training on the competence of the training alumni is to conduct an assessment of the achievement of objectives, and the standard competence that have been set. In this case, the standard competence which is used is based on the Regulation of the Minister of Administrative Reform and Bureaucratic Reform of the Republic of Indonesia Number 38 of 2017 which is concerning about Competency Standards for State Civil Apparatus Positions